2010
DOI: 10.1155/2010/314213
|View full text |Cite
|
Sign up to set email alerts
|

Electrodelivery of Drugs into Cancer Cells in the Presence of Poloxamer 188

Abstract: In the present study it is shown that poloxamer 188, added before or immediately after an electrical pulse used for electroporation, decreases the number of dead cells and at the same time does not reduce the number of reversible electropores through which small molecules (cisplatin, bleomycin, or propidium iodide) can pass/diffuse. It was suggested that hydrophobic sections of poloxamer 188 molecules are incorporated into the edges of pores and that their hydrophilic parts act as brushy pore structures. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…A similar study has been reported with docetaxel or paclitaxel loaded PLGA and poloxamer blend NPs wherein drug loaded PLGA poloxamer blend NPs showed potent efficacy in drugresistant human breast cancer cells due to increased uptake and enhanced release [6,9]. Poloxamer has been reported to enhance the transfection efficiency by minimizing the cell injury due to electric shock [10,11]. Amphiphilic GC, a water-soluble chitosan derivative at physiological pH 7.4, has been widely used in the formulation of anti-cancer drugs, nucleic acid transfection and imaging agents for diagnostic purposes [12][13][14][15][16][17][18].…”
Section: Introductionsupporting
confidence: 54%
“…A similar study has been reported with docetaxel or paclitaxel loaded PLGA and poloxamer blend NPs wherein drug loaded PLGA poloxamer blend NPs showed potent efficacy in drugresistant human breast cancer cells due to increased uptake and enhanced release [6,9]. Poloxamer has been reported to enhance the transfection efficiency by minimizing the cell injury due to electric shock [10,11]. Amphiphilic GC, a water-soluble chitosan derivative at physiological pH 7.4, has been widely used in the formulation of anti-cancer drugs, nucleic acid transfection and imaging agents for diagnostic purposes [12][13][14][15][16][17][18].…”
Section: Introductionsupporting
confidence: 54%
“…The electroporation was performed by an electroporator Chemopulse III, generating bipolar pulses, used for both in vivo and in vitro studies [3,4,6,7,15,21]. Briefly, the instrument is equipped with a large voltage control within 100–2,200 V, simplified operations, a lock against unauthorized manipulations, a battery supply, an enhanced protection against electrical hazards, an autonomy providing more than 200 electroporations with one battery charge, and a recharging time for a depleted battery of less than 10 hours [6].…”
Section: Methodsmentioning
confidence: 99%
“…the instrument is equipped with a large voltage control in the limits of 100-2200 V, simplified operations, locking against illegal manipulations, a battery supply, enhanced protection against electrical hazards both for the patient and the physician, autonomy providing for more than 200 electroporations with one battery charge, and a recharging time for a depleted battery of less than 10 hours (19). the electrotreatment was done by 16 biphasic pulses, each of them 50+50 µs duration with 20 ms pause between both phases and pause between bipolar pulse of 880 ms. thus, the total duration of the series reached 15.1 ms. At that frequencies and voltages it was proved that the effectiveness of the electroporation is high and the sensation for pain is minimal A pair of parallel flat electrodes with the adjustable inter electrode distance (caliper type) in the range 5-30 mm were used.…”
Section: Methodsmentioning
confidence: 99%